Effects of water deficit on the activity of nitrate reductase and content of sugars, nitrate and free amino acids in the leaves and roots of sunflower and white lupin plants growing under two nutrient supply regimes - Correia, Maria João (2005)
The effects of a two weeks soil drying period on the activity of nitrate reductase (NR; EC 1.6.6.6) were studied on Helianthus annuus L. and non-nodulated Lupinus albus L. plants, growing under two nutrient supply regimes. NR activity was assessed in leaf and root extracts, by measuring the activity of the unphosphorylated active form (NRact), the maximal extractable activity (NRmax) and the activation state. To get insight into potential signalling compounds, nitrate, amino acids and soluble sugars concentrations were also quantified. On both species, foliar NRact and NRmax were negatively affected by soil drying and reduced supply of nutrients, the observed changes in NR activity being linearly-correlated with the depletion of nitrate. Similar results were obtained in the roots of sunflower. Conversely, in white lupin roots NRmax was found to be independent of tissue nitrate concentration. Regardless of the species and organ, the activation state of the enzyme was unaffected by the nutrient supply regime. In well-watered sunflower roots only about 50% of the existing NR was unphosphorylated, but the activation state increased significantly in response to drought. In contrast, lupin roots always exhibited NR activation state values close to 80% or even higher. At the leaf level, NR activation state was hardly changed in response to soil drying. The contribution of changes in the concentrations of soluble 5 sugars and amino acids to explain the observed variations in NR activity are discussed.